PENGELOMPOKAN POHON INDUK CENGKEH TERPILIH DI KABUPATEN SUMEDANG BERDASARKAN KARAKTER MORFOLOGI / Clustering of Progeny Clove Accessions from Cimanggu Population in Sumedang Based on the Morphologycal Characters - Cheppy Syukur; nFN Sukarman; Nurliani Bermawie (Pusat Penelitian dan Pengembangan Perkebunan, 2016)
Cimanggu progeny clove has been distributed to almost of centre production, such as in Sumedang. However, their genotypes are still unidentified. Therefore, clustering cloves accession population in Sumedang is necessary. The objectives of this study is to cluster and determine phylogenetic relationship of Cimanggu progeny clove population in Sumedang base on morphological characters. The experiment was conducted in Sumedang (West, Java) from 2013 until 2014, by using 10 selected accessions (healthy, more than 40 years old, productivity is ≥ 20 kg dried flower). Variables were observed include morphological leaf, flower and flower production. To distinguish genotype from each accession was conducted by cluster analyzed, while to identify the variables which were related to the clusters formation, used correspondence analysis. The results indicated, that clove population Sumedang can be classified into three clusters as followed: the first cluster are Syar 43 and 46 accessions, characterized by greenish orange and greenish purple of young leaves tip with flower tube greenish red (GR 180B), the second cluster are Syar 44 and 45 accession, characterized by tip reddish purple young leaves and greenish red (GR181B) flower tubes color, and the third cluster are Syar 47, 49, 50, 51 and 52 accessions, characterized by orange young leaves tips and greenish red (GR180C) flower tubes. This information can be utilized to support releasing Cimanggu clove variety.Keywords: Syzygium aromaticum, clustering, characters, morphology